Basal cell nevus syndrome or Gorlin syndrome. - Bonifazi, E.; Milano, A.; Inverardi, D. (European Journal of Pediatric Dermatology, 2004)
Basal cell nevus syndrome or Gorlin syndrome (2) is an inherited autosomal dominant disorder, due to a mutation of the tumor suppressor gene PTC, which is involved in both organogenesis and carcinogenesis. It often starts at puberty with relapsing odontogenous cysts (1), which lead to loss of the teeth. Starting from infancy (3) on the trunk, neck, face and upper limbs appear multiple, apparently trivial nevus-like lesions, which histologically are basal cell carcinomas. After puberty these lesions get more aggressive and may ulcerate. There are also numerous dysmorphisms, palmar and plantar pits, ectopic calcifications of the falx cerebri, mental retardation and tumors affecting various organs. All the suspected lesions should be treated, the patients should be monitored searching for initial malignancy and their relatives should be investigated to unveil minimal forms.